Breast Involvement in Anti-Neutrophil Cytoplasmic Antibodies Positive Granulomatosis With Polyangiitis in a 64-Year-Old Female Patient - Monika RYBA,; Andrzej KONIECZNY,; Zbigniew HRUBY, (Archives of Rheumatology, 2017)
In this article, we present a case of a female patient suffering from granulomatosis and polyangiitis with active glomerular disease, who developed exacerbation of pulmonary vasculitis and palpable tumors of right breast. A possibility of neoplastic disease was excluded by histopathological examination of percutaneous biopsy specimen, revealing granulomatous inflammatory infiltrate, without any features of neoplasia. Moreover, both pulmonary and breast lesions subsided following intensification of immunosuppressive/antiinflammatory treatment.